Changing forest coverage and understanding of deforestation in Nepal Himalayas - Chapagain, Prem Sagar; Aase, Tor H. (Geographical Journal of Nepal, 2020)
The environmental situation of the Hiamlayas is a matter of global concern. Understanding on Himalayas environment is usually shaped by the changing views expressed by research institutions, doner organizations, and finally by politics and power relations. In line with changing paradigms in knowledge-producing institutions, different understandings of environmental challenges in the Himalayas have emerged. Based on the literature and available data, we have tried to discern changes in forest policies, their implication on forest management and various understandings of deforestation in Nepal Himalayas that are salient in the scientific literature. The debate of deforestation/degradation on the state of Himalayan environment came on the global agenda in the 1950s. The initial focus was on population growth and pressure on natural resources. It was followed by attention to processes of development and physical interventions in a fragile environment. Most recently local participation and poverty alleviation have been high on the agenda. In this context, the present paper attempts to examine the debates in the light of recent events and circumstances related to environmental processes in general and forest management of Nepal in particular.